PEMANFAATAN LINGKUNGAN SEBAGAI SUMBER BELAJAR DALAM MENINGKATKAN MAHĀRATUL KALĀM PADA PELAJARAN BAHASA ARAB KELAS 1 MTS HIDAYATUNNAJAH - Qotrunnada, Zahrotul; Hendra, Faisal (CV. Lafadz Jaya, 2024)
Utilization of the environment as a learning resource in improving students' Mahāratul Kalām (speaking skills) in grade 1 Arabic subjects at MTS Hidayatunnajah. The four language skills for learning Arabic are istima' (listening), qiro'ah (reading), and kitabah. Mahāratul Kalām (speaking skills) is one of the four (writing). The environment makes students improve linguistic and non-linguistic as they learn Arabic. To examine the obstacles to learning Mahāratul Kalām Arabic, this research combines a qualitative approach with analytical descriptive methods. Students in grade 1 Arabic subjects at MTS Hidayatunnajah became research participants. The study found that there was an increase in environmental utilization as well as teachers should work to improve their students' motivation, memory, and speaking practice.